2022
DOI: 10.3390/toxics10060307
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Thirdhand Smoke Exposure after Short Visits to Public Facilities (Noraebang and Internet Cafés): A Prospective Cohort Study

Abstract: We aimed to evaluate the degree of thirdhand smoke (THS) caused by short-term exposure to smoking-related substances. To this end, we evaluated the change in concentration of a smoking-related urine biomarker in volunteers before and after visiting public spaces where there is likely THS exposure. We hypothesized that a visit to such public spaces would result in an increase in such biomarkers. Participants visited one of the predetermined facilities (noraebang, PC café) and revisited the same facility after 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Thirdhand smoke is when an individual is exposed to substances released to the air after being absorbed into the smoker's body, clothes, walls, or curtains, even if they are not exposed to the cigarette smoke caused by others. Recent studies have reported increased urine cotinine due to thirdhand smoke, even when not exposed to secondhand smoke [26][27][28] . Second, self-report cannot measure exposure in all settings.…”
Section: Discussionmentioning
confidence: 99%
“…Thirdhand smoke is when an individual is exposed to substances released to the air after being absorbed into the smoker's body, clothes, walls, or curtains, even if they are not exposed to the cigarette smoke caused by others. Recent studies have reported increased urine cotinine due to thirdhand smoke, even when not exposed to secondhand smoke [26][27][28] . Second, self-report cannot measure exposure in all settings.…”
Section: Discussionmentioning
confidence: 99%
“…THS refers to exposure to indirect smoking through tobacco residue that is adsorbed into surfaces within an environment and is re-emitted to the individual remaining in the same space afterward [18,19]. Studies have reported that individuals in these circumstances do not recognize tobacco smoke, and even short-term exposure through THS can elevate cotinine concentrations in the body [20]. SR only reflects second-hand smoke and cannot reflect THS.…”
Section: Measurement Of the Prevalence Of Active And Passive Smokingmentioning
confidence: 99%